Beyond Container: Postmodern Packaging as Visual Communication Medium in Contemporary Branding Strategy - Setiawardhani, Widya Oktaryi (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research investigates the impact of postmodern aesthetics on product packaging design, identifies defining visual elements, evaluates young consumers' perceptions, and examines the effects on branding strategies and purchasing behavior, focusing on postmodern principles like deconstruction, intertextuality, irony, and hybridity. Materials and methods: A qualitative approach with descriptive-analytical methods is adopted through a multiple case study design, utilizing literature reviews and non-participatory visual observation of postmodern packaging characteristics, analyzing aspects such as typography, illustrations, layout, colors, materials, and effects, with data analyzed through visual semiotic and comparative methods. Results: Key findings indicate postmodern influences in packaging design manifest through experimental typography, contrasting colors, non-linear layouts, and mixed media, employing strategies like humor and irony, exemplified by anti-theft lunch bags and interactive packaging; postmodern design merges aesthetic and functional appeal, with typography serving as dual visual communication. Conclusions: Postmodern packaging reflects a transformative shift from simple containers to intricate visual communication that conveys symbolic messages and emotional expression, offering designers expressive freedom and serving as a strategy for enhancing product appeal; the synergy of aesthetic, emotional, and functional elements fosters memorable consumer experiences in a competitive market, positioning postmodern design as significant in contemporary practices responsive to socio-cultural dynamics and market evolution.